Associations Between Parity, Breastfeeding, and Risk of Maternal Type 2 Diabetes Among Postmenopausal Women. Issue 3 (September 2019) - Luo, Juhua; Hendryx, Michael; LeBlanc, Erin S.; Shadyab, Aladdin H.; Qi, Lihong; Sealy-Jefferson, Shawnita; Manson, JoAnn E.
Abstract : OBJECTIVE: To examine associations among parity, breastfeeding history, and risk of developing type 2 diabetes among postmenopausal women. METHODS: A prospective cohort study was conducted. One hundred thirty-six thousand six hundred fifty-two postmenopausal women aged 50–79 years participating in the Women's Health Initiative recruited from 40 clinical centers throughout the United States between 1993 and 1998, without baseline cancer or diabetes were followed for 14.2 years. Parity and breastfeeding data were collected by questionnaires administrated to all participants at baseline. Incident diabetes was assessed via validated self-report of physician-diagnosed diabetes treated with insulin or other hypoglycemic medications. Multivariable Cox proportional hazards regression models were used to assess associations between parity, breastfeeding and diabetes incidence, and racial–ethnic differences in the associations. RESULTS: During follow-up, 18, 812 cases of incident diabetes were identified. Overall, a greater number of term pregnancies was associated with increased risk of diabetes ( P for trend=.002), and longer duration of breastfeeding was associated with lower risk of diabetes ( P for trend <.01). After further adjusting for adult weight gain among a subset of the cohort (n=75, 558) with 9, 110 cases, the association between parity and risk of diabetes were attenuated and became nonsignificant. Also, parous women with fewer than five term pregnancies did not have increased diabetes risk when breastfeeding for 3 months or more per child, which was associated with less weight gain. CONCLUSION: The results of this large, prospective study showed that the association between parity and risk of type 2 diabetes was most likely confounded by adult weight gain among postmenopausal women. Abstract : The risk of diabetes among postmenopausal women can be reduced by preventing adult weight gain.